The Dorsal Periosteal Curtain for Distal Radius Osteotomy Via the Volar Approach. Issue 3 (September 2021) - Potter, J. Alexa; Ross, Mark
Abstract : Volar wedge osteotomy and angle stable volar plating is now considered a standard approach for correction of distal radius malunion. In previous descriptions of the technique, soft tissue release has been performed with periosteal incision in line with the bony osteotomy. We present a technique whereby the dorsal periosteum is incised more proximally creating a dorsal vascularized periosteal "curtain." Our technique has several advantages including systematic release of restraining soft tissues to allow better distraction and reduction of the malunion; a dorsal periosteal curtain of vascular tissue with which to contain bone graft, protect extensor tendons and expedite healing; and better access to locally available bone graft. The previously described rotation-advancement of pronator quadratus is also used for plate coverage. We have found this technique straightforward to execute and teach, and useful in mitigating against some of the potential risks of the standard technique.